Mutations in exon 11 (11.1 and 11.2) of the BRCA1 gene and risk factors for breast cancer in Burkina Faso - Isabelle T. Kiendrebeogo; Abdou A. Zoure; Fabienne I. Zongo; Abdoul K. Ouattara; Marie N.L. Ouedraogo; Jospin Amegnona; Albert T. Yonli; Bagora Bayala; Nayi Zongo; Aboubacar H. Bambara; Alexis Y. Sawadogo; Theodora M. Zohoncon; et al. (AOSIS, 2022)
Breast cancer is the leading cause of death among women in both developed and developing countries. It is multifactorial, including genetic predispositions such as oncogenic mutations on BRCA1 and 2 genes. The objectives of the present study were to identify oncogenic mutations in exon 11 of the BRCA1 gene and to determine the risk factors for breast cancer among women population in Burkina Faso. This study involved 100 women, including 50 cases of breast cancer and 50 controls (no clinical signs and no family history of breast cancer or other cancers). Mutations in the BRCA1 gene were detected by PCR using sequence primers specific for exon 11 fragments (11.1 and 11.2). In our study population, age (OR=22.40; CI: 4.33-115.82; p0.001) and obesity (OR=4.23; CI: 1.64-10.92; p=0.003) were risk factors while multiparity was a protective factor for breast cancer (OR=0.35; CI: 0.15-0.81; p=0.02). A mutation was found on both fragments 11.1 and 11.2 of the BRCA1 gene exon 11 in 04/50 (8.0 %) of patients. No mutations were observed in controls. The present study revealed high frequency of oncogenic mutations in exon 11 fragments (11.1 and 11.2) of the BRCA1 gene. These mutations on exon 11 are and involved in the occurrence of breast cancer in our population. Age and obesity were also risk factors for breast cancer among women population in Burkina Faso.